Three stage dynamic heuristic for multiple plants capacitated lot sizing with sequence-dependent transient costs. (January 2019) - Abdullah, Sari; Shamayleh, Abdulrahim; Ndiaye, Malick
Highlights: Motivated by real problem for one of the world biggest chemical companies. Demand planning problem for a petrochemical industry four tiers supply chain. Dynamic Iterative 3-stage Dynamic heuristic for the NP hard problem. Quality solutions and acceptable computational time provided by the heuristic. Abstract: In this paper we investigate the demand planning problem for a petrochemical industry four tiers supply chain that integrates lot-sizing, scheduling with sequence dependent transient costs, transportation and warehousing decisions between suppliers, plants, warehouses, and customers. The problem was modeled using Mixed-Integer Linear Programming (MILP) and featuring a setup carryover and sub-tours elimination constraints. The problem is NP-Hard; therefore, an iterative three stage heuristic was developed which provides quality solutions with a very acceptable computational time. The heuristic computational efficiency was tested on different problem instances of different sizes, and the reported results were within a range of 0.09–2.00% gap from optimality.